1989
DOI: 10.1113/jphysiol.1989.sp017534
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of simulated ischaemia on intracellular Ca2+ and tension in isolated ferret ventricular muscle.

Abstract: SUMMARY1. In order to study cellular events occurring in ischaemia, we have developed a method for simulating ischaemia in an isolated papillary muscle. Muscles were suspended in a chamber and changed from conventional superfusion with Tyrode solution to gas perfusion with 95% N2/5 % CO2 (N2 gas perfusion), thus simultaneously stopping oxygenation and flow. Surface cells of the preparation were injected with the photoprotein aequorin in order to monitor intracellular free calcium2. Gas perfusion with 95% 02/5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
1

Year Published

1992
1992
1995
1995

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 49 publications
6
52
1
Order By: Relevance
“…Allen et al 1989;Lee & Allen, 1991). However, this approach is complicated by the need to estimate the degree of activation of the intact preparations (see Eisner et al 1987b, andAllen et al 1989, for discussion). An 470 CAUSES OF ISCHAEMIC CONTRACTILE FAILURE alternative is to try to mimic the metabolic changes accompanying ischaemia in a model with continued perfusion.…”
Section: Metabolic Changes During Exposure To Cn-and Chcmentioning
confidence: 99%
See 2 more Smart Citations
“…Allen et al 1989;Lee & Allen, 1991). However, this approach is complicated by the need to estimate the degree of activation of the intact preparations (see Eisner et al 1987b, andAllen et al 1989, for discussion). An 470 CAUSES OF ISCHAEMIC CONTRACTILE FAILURE alternative is to try to mimic the metabolic changes accompanying ischaemia in a model with continued perfusion.…”
Section: Metabolic Changes During Exposure To Cn-and Chcmentioning
confidence: 99%
“…This is supported by the finding that the acidosis which accompanies anoxia is increased in size in the presence of extracellular lactate (Ellis & Noireaud, 1987) or in the presence of a-cyano-4-hydroxycinnamate. However, a further mechanism which may contribute to the intracellular acidosis is the accumulation of CO2 within the cell (see Allen et al 1989, for a discussion of this effect).…”
Section: Metabolic Changes During Brief Periods Of Ischaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, a proton-induced slowing of Ca2" uptake by the sarcoplasmic reticulum (Mandel et al 1982) (Earm & Irisawa, 1986) and since Ca2" is normally extruded by the Na'-Ca2+ exchanger in resting muscle (for review see Eisner & Lederer, 1989) (Kleber, 1983). It is also likely that changes in the action potential which become prominent after 10-15 min are involved in the subsequent decline in Ca2`transients which occurs later in ischaemia (Allen et al 1989). (ii) A number of studies have suggested that operation of the Na+-H+ exchanger leading to Na+ and Ca2`loading is the mechanism by which acidosis causes increased [Ca2+], during ischaemia (Tani & Neely, 1989;Pike, Kitakaze & Marban, 1990 (Kleber, 1983;Vanheel et al 1990) and, as noted above, Vanheel et al suggested that extracellular acidosis was inhibiting the exchanger. This was also the basis for the hypothesis of Lazdunski et al (1985) in which it was proposed that reactivation of the Na+-H+ exchanger on reperfusion led to Na+ and therefore Ca2`loading.…”
Section: Calibration Offura-2 Signalsmentioning
confidence: 99%
“…However, our result is close to the predictions of data of Vaughan-Jones and colleagues. They showed that a reduction in pH0 from 7-4 to 6-4 caused approximately a 5-fold fall in proton efflux (Vaughan-Jones & Wu, 1990b) while a decrease in pHi from 7-15 to 6-68 caused approximately a 5-to 10-fold increase in proton efflux (Kaila & Vaughan-Jones, 1987 Allen et al 1989). Since fura-2 was found to be sensitive to changes of pH it was necessary to correct the [Ca2+]i using the changes of pH, measured during lactate exposure.…”
Section: Calibration Offura-2 Signalsmentioning
confidence: 99%